Sensitivity analysis on the microwave heating of coal: A coupled electromagnetic and heat transfer model. (5th November 2017) - Lin, Baiquan; Li, He; Chen, Zhongwei; Zheng, Chunshan; Hong, Yidu; Wang, Zheng
Highlights: A coupled electromagnetic and heat transfer model was built for microwave heating. An optimal frequency of 2.45 GHz was found to achieve efficient heating. Increase in the MW power contributes to the thermal heterogeneity. Temperature increases while thermal heterogeneity decreases with loss factor. Abstract: Microwave irradiation has gained widespread popularity in coal processing. However, the effects of microwave parameters and coal properties on the heating behavior remain much less explored. In this study, a coupled electromagnetic and heat transfer model was developed to investigate the microwave-coal interactions. Results show that microwave heating is sensitive to frequency: an optimal frequency of 2.45 GHz was found whereby the maximum temperature and energy efficiency can be achieved. In addition, the increase in the microwave power contributes to the thermal heterogeneity and energy consumption, suggesting that low powers are suitable for uniform heating and energy saving, while high powers apply to differential and rapid heating. As the loss factor increases, the temperature and energy efficiency increase while the thermal heterogeneity decreases. Increasing the loss factor could not only achieve rapid and uniform heating but also save energy. Furthermore, the optimal coal size for enhancing microwave energy absorption could be obtained when the coal diameter is 50 mm, with heights ranging from 60 mm to 100 mm. Outcomes of this study can be used to identify the electric and thermal fields of coal and thereby help to optimize the microwave applicators.